Estudo comparativo da resistência à corrosão dos aços inoxidáveis super duplex ASTM A890 / A890M grau 5A e 6A - Martins, Alessandra Souza (2014)
The super duplex stainless steel is wide ly used in aggressive corrosion environments. This type of steel has attractive combination of good mechanical strength in addition to excellent corrosion and i mpact resistance. However, when undergoing a heat treatment in temperature range between 300 °C and 550 °C a precipitation of α ' - phase can occur causing a reduct ion of corrosion resistance and ductility. Th erefore, the aim of this study is to evaluate the corrosion resistance of super duplex stainless steel grade 5A and 6A aft er heat treatment at 475 °C for different aging time. The difference in chemical composition between these steel grades is in copper and tungsten content. The corr osion resistance of the samples was evaluated employing following electrochemical techniques: open circuit potential measurement, anodic polarization, cyclic polariza tion, electrochemical impedance spectroscopy and critical p itting temperature. The ele ctrochemical results indicate a strong influence of aging time on corrosion resistance. Microstructural examination revealed a dual phase structure composed of a ferritic matrix with austenite islands in equal proportion. The hard ness increases rapidly in the early hours of heat treatment, then with progressing time the hardening rate decreas es. The electrochemical results indicated that for both steel types studied, the samples with 10 hours of heat treatment had a higher corrosi on resistance.